2016
DOI: 10.1093/mnrasl/slw189
|View full text |Cite
|
Sign up to set email alerts
|

The stellar halo in the inner Milky Way: predicted shape and kinematics

Abstract: We have used N-body simulations for the Milky Way to investigate the kinematic and structural properties of the old metal-poor stellar halo in the barred inner region of the Galaxy. We find that the extrapolation of the density distribution for bulge RR Lyrae stars, ρ ∼ r −3 , approximately matches the number density of RR Lyrae in the nearby stellar halo. We follow the evolution of such a tracer population through the formation and evolution of the bar and box/peanut bulge in the N-body model. We find that it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 40 publications
7
34
0
Order By: Relevance
“…In the upper left panel of Figure 6, we show the density as a function of galactocentric radius in each θ bin. It is noteworthy that, as predicted by Pérez-Villegas et al (2016, Fig. 1), these densities appear to smoothly connect the RR Lyrae densities measured near the Sun to those measured in the Bulge.…”
Section: A Sample Of Rr Lyrae With Transverse Velocitiessupporting
confidence: 79%
“…In the upper left panel of Figure 6, we show the density as a function of galactocentric radius in each θ bin. It is noteworthy that, as predicted by Pérez-Villegas et al (2016, Fig. 1), these densities appear to smoothly connect the RR Lyrae densities measured near the Sun to those measured in the Bulge.…”
Section: A Sample Of Rr Lyrae With Transverse Velocitiessupporting
confidence: 79%
“…The outer rotation of the CB is similar to the Model 1 of B17, which obtained all its rotation from the angular momentum transfer from the bar (Saha et al 2016). The increase of the rotation of the inner spheroid at this radius is not unexpected, as for example it is also observed in the Milky Way's inner stellar halo (Ness et al 2013;Perez-Villegas et al 2017).…”
Section: Stellar Kinematicssupporting
confidence: 79%
“…Moreover, on even longer time-scales, box/peanut bulges and bars can interact through resonances with the disc and thereby redistribute its material, generating for example surface brightness breaks, as well as ring-like substructures (Buta & Crocker 1991;Debattista et al 2006;Erwin et al 2008;Buta 2017). Bars also transfer their angular momentum to the spheroid components, such as classical bulges (Saha et al 2012(Saha et al , 2016, stellar haloes (Perez-Villegas et al 2017) and dark matter haloes (Athanassoula & Misiriotis 2002), changing their dynamical properties. Furthermore, Erwin & Debattista (2016) show also with observations that classical bulges can coexist with discy pseudobulges and box/peanut bulges building composite bulges, a scenario that has also been reproduced in galaxy formation simulations (Athanassoula et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Meléndez et al 2008;Alves-Brito et al 2010;Ryde et al 2010;Gonzalez et al 2011;Johnson et al 2014;Gonzalez et al 2015;Ryde et al 2016;Jönsson et al 2017;García Pérez et al 2018 Kunder et al (2016) suggested that the observed spatial distribution and kinematics are consistent with a classical bulge origin, although they cannot rule out the possibility that they are the metal-poor tail of a more metal-rich halo-bulge population. Instead, Pérez-Villegas et al (2017) showed that RRLyrae stars in the bulge might be the inner extension of the Galactic stellar halo.…”
Section: Introductionmentioning
confidence: 99%